Tourist Image Building of the Country: Application of the Historiographical Method - AFANASYEV, Oleg Evgenievich (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020, 2020)
The article deals with the problem of using the principles of the historiographical approach in the study of the reasons and factors for the tourist image building of the country in the historical and chronological aspect. The authors consider the importance of studying the historical process of creating negative or neutral images of Russia among European residents, based on the historiographical analysis of the sources of the 13th-19th centuries, which in the current context directly influences the demand and interest in tours to the country. The article offers and discusses in detail the mechanisms of tourist image building of the country in its two aspects – subjective and objective. It is noted that any person's image of a particular country without having visited it directly can be considered subjective, and be potentially attractive, neutral, or repellent. The negative image of Russia in the public perception of European residents over a long historical period is now expressed in its negative tourist image and fears of a possible tourist trip to the country. The article describes the technology of applying the historiographical analysis in the practice of training and retraining of industry professionals who are trained in technologies for designing tourist images of the country's regions. The article presents methods and forms of working with historical sources to identify ideas about the hospitality traditions and tourist images of Russia, described in the works of foreign travelers of the 13th-19th centuries. Descriptions of the peoples of Russia, their life and customs contained in these works, built the image perception of the country in the minds of European residents, in some cases with extrapolation effect to the modern era. The article states the empirical effectiveness of using historiographical analysis technologies to assess the causes and consequences of building a negative or neutral tourist image of Russia among foreign tourists, conditioned by the trends of its descriptions in historical sources. The conclusion is made that it is necessary to develop marketing strategies to overcome negative images and perceptions of Russia among potential consumers of its tour programs.